Canadian Thoracic Society Guidelines for Occupational Asthma. Issue 4 (3rd August 1998) - Tarlo, Susan M; Boulet, Louis-Philippe; Cartier, André; Cockcroft, Donald; Côtè, Johanne; Hargreave, Frederick E; Holness, Linn; Liss, Gary; Malo, Jean-Luc; Chan-Yeung, Moira
Abstract : OBJECTIVE: To provide broad guidelines and principles to help primary care physicians, occupational physicians, allergists and respirologists with the recognition, diagnosis and management of patients with occupational asthma (OA). OPTIONS: These guidelines are mainly directed towards OA induced by a workplace sensitizing agent. However, irritant-induced asthma and workplace aggravation of underlying asthma are also addressed, and some consideration is given to other differential diagnoses. OUTCOMES: To enable the assessing physician to investigate patients with possible OA appropriately and to provide guidelines for appropriate early referral when specialized investigations are required. To provide an understanding of the appropriate management strategies following objective diagnosis. EVIDENCE: The key diagnostic and management recommendations were based on a critical review of the literature and by specialist consensus meetings. VALUES: Evidence was categorized as follows. Level 1: Evidence from at least one randomized, controlled trial. Level 2: Evidence from at least one well-designed clinical trial without randomization, from cohort or case-control analytical studies, preferably from more than one centre, from multiple time series or from dramatic results in uncontrolled experiments. Level 3: Evidence from the opinions of respected authorities based on clinical experience, descriptive studies or reports of expert committees. Evidence was further subdivided as follows: A. Good evidence to support a recommendation for use; B. Moderate evidence to support a recommendation for use; C. Poor evidence to support a recommendation for or against use; D. Moderate evidence to support a recommendation against use; E. Good evidence to support a recommendation against use. BENEFITS, HARM AND COSTS: The medical and socioeconomic risks and benefits of an incorrect diagnosis of OA and of failure to diagnose true OA were considered in the recommendations. VALIDATION: The document has been reviewed and endorsed by the Canadian Thoracic Society, the Canadian Society of Allergy and Clinical Immunology, and The College of Family Physicians of Canada. CONCLUSIONS: There is good evidence for rapid investigation and objective categorization of presented symptoms into OA, aggravation of underlying asthma, unrelated asthma or other diagnoses. OA should be suspected in all adult onset asthmatics whose asthma begins or worsens while they are working. Investigations should be directed to an objective assessment of asthma and then to an assessment of the work relationship, using a combination of investigations as feasible, which may include immunological tests, pulmonary function assessed during work periods and away from work, and specific challenge tests. Early specialist referral is recommended for diagnosis. Management strategies include general asthma management in addition to measures to avoid further exposure to a relevant workplace sensitizer. Compensation issues and other workers at risk of developing OA also need to be considered when the diagnosis is made.